PENGARUH KEPEMIMPINAN INOVATIF DAN MOTIVASI TERHADAP BUDAYA KERJA DAN PEMBERDAYAAN DI KABUPATEN MALUKU TENGGARA BARAT - Agusthina Risambessy (Journal of Economics Review (JOER), 2022)
This study aims to analyze and explain: the influence of innovation leadership on work culture, the effect of motivation on work culture, the influence of innovation leadership on empowering community groups through work culture, the effect of work motivation on empowering community groups through work culture, the influence of work culture on empowering community groups. The object of research in West Southeast Maluku Regency, using the path analysis method. The sampling technique used purposive random sampling. The sample in this study is a community empowerment group.The results of the study prove that: innovation leadership has a significant positive effect on work culture, motivation has a significant positive effect on work culture, innovation leadership has a positive significant effect on empowerment through work culture. Motivation has a significant positive effect on empowerment through work culture. Work culture has a significant positive effect on empowerment in West Southeast Maluku Regency. For future researchers, it is necessary to study collaborative knowledge sharing and innovation leadership in the framework of developing community groups in the future